2010
DOI: 10.1002/bit.22769
|View full text |Cite
|
Sign up to set email alerts
|

Cell line‐specific control of recombinant monoclonal antibody production by CHO cells

Abstract: In this study we compare the cellular control of recombinant human IgG 4 monoclonal antibody (Mab) synthesis in different CHO cell lines. Based on comprehensive empirical analyses of mRNA and polypeptide synthetic intermediates we constructed cell line-specific mathematical models of recombinant Mab manufacture in seven GS-CHO cell lines varying in specific production rate (qMab) over 350-fold. This comparative analysis revealed that control of qMab involved both genetic construct and cell line-specific factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
141
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(163 citation statements)
references
References 67 publications
21
141
1
Order By: Relevance
“…In fact, CHO cells are known for being able to adapt to changes in process conditions, which has been exploited in the industry to generate clonally derived cell lines with enhanced manufacturing capabilities (Frye et al, 2016). Moreover, the majority of cells in host cell lines seem to be intrinsically incapable of high production of MAb, and universally competent cells are likely relatively rare cases (O'Callaghan et al, 2010). Functional heterogeneity residing in the host cell population is typically referred to as clonal variation (Fig.…”
Section: Clonal Variationmentioning
confidence: 99%
“…In fact, CHO cells are known for being able to adapt to changes in process conditions, which has been exploited in the industry to generate clonally derived cell lines with enhanced manufacturing capabilities (Frye et al, 2016). Moreover, the majority of cells in host cell lines seem to be intrinsically incapable of high production of MAb, and universally competent cells are likely relatively rare cases (O'Callaghan et al, 2010). Functional heterogeneity residing in the host cell population is typically referred to as clonal variation (Fig.…”
Section: Clonal Variationmentioning
confidence: 99%
“…Several studies have investigated the underlying bottlenecks that limit cell specific productivities with, in part, contradictory results. This is not surprising in view of the phenotypic and genomic diversity observed in CHO cells [4][5][6]. Although the precise genes involved vary from case to case, certain cellular pathways and functions are frequently found to influence cellular productivity (Table 1).…”
Section: Introductionmentioning
confidence: 96%
“…These studies were initially driven by the hope of finding the rate limiting step for protein production and identify the one gene or the few genes that would either increase cellular productivity if appropriately engineered, or that would allow the efficient identification of high producing cell lines. However, by now it has been acknowledged that it is not a single step or even pathway that controls productivity but the coordinated interplay and cooperation of multiple steps, none of which must be allowed to become limiting, and all of which have to be expressed and active in a balanced way [4,7,8]. In fact, Clarke et al 2011 found a set of 287 genes for the prediction of cellular productivity in the model they established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heavy and light chains are connected by several inter-and intra-disulfide bonds. The assembly of heavy and light chains inside the ER is strictly controlled (O'Callaghan et al 2010). The heavy chains cannot be secreted without being assembled with the light chains because the CH1 domain controls the assembly and secretion of IgG (Feige et al 2009).…”
Section: Introductionmentioning
confidence: 99%